Individual Grievance Procedures in United National Secretariats - Beigbeder, Yves (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1982)
The author examines the particular way by which grievances of the 46 000 United Nations employees are settled.